Oxidative dehydrogenation activity of high-silica Co-zeolitesinfluecence of presence of ammonia - Novoveská, Kateřina; Bulánek, Roman; Wichterlová, Blanka (Univerzita Pardubice, 2002)
The aim of this study is to bring a view on possibility to use high-silica zeolites modified with ion-exchanged Co 2+ ions in oxidative dehydrogenation and ammoxidation of propane. The MFI zeolites chosen are known to possess catalytic activity in ammoxidation of ethane. A set of samples with different content of ionexchanged cobalt, different Si/Al rations and type of co-cations was prepared. The courses of reaction of propane with oxygen or oxygen and ammonia were measured in dependence on temperature. Co-MFI zeolites exhibited catalytic activity in oxidative dehydrogenation of propane to propene and ammoxidation of propane led to formation of acetonitrile. The formation of acetonitrile is explained by destruction of acrylonitrile formed.
Keywords: Oxidativní dehydrogenace; zeolity; katalytické procesy